Pengaruh Komite Audit, Profitabilitas, Ukuran Perusahaan Terhadap Tax Avoidance - Selvi Diana Rosyidah; Faif Nafif; Jumaiyah Jumaiyah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
Profit is the basis in determining the tax burden. Tax avoidance is an action to reduce tax obligations from the provisions of tax law. The purpose of this study is to examine and analyze the effect of the audit committee, profitability, and company size on tax avoidance in coal mining sector companies listed on the IDX for the 2016-2018 period. The type of research used is quantitative research. The data collection method used in this study is a documentation technique using the types and sources of secondary data. The analytical technique used in this research is multiple linear regression analysis. The sample selection used a purposive sampling method with a total sample of 39 coal mining sector companies listed on the IDX for the 2016-2018 period. The results of this study indicate that the audit committee calculated by the number of audit committees has no effect on tax avoidance. Profitability calculated by ROA has a significant negative effect on tax avoidance. Firm size calculated by Ln (Total Assets) also has no effect on tax avoidance.